Effect of Use of Educational Appearance Ape (APE) Media Image to Creativity Children Age 4-5 Years in National Country City Mataram , West Nusa Tenggara - I Made Suwasa Astawa; Ni Wayan Purni Astiti (International Journal of Emerging Issues in Early Childhood Education, 2019)
Problems found in developing children's creativity in children age national country city Mataram West Nusa Tenggara. is the non-use of educational game tools provided by schools. Educational game tools that exist only to be stored in the warehouse and never applied in children's learning. Teachers are more monotonous to teach using magazines and children's books. The type of research used is experiment with Randomized Pretest-Postest Control Group Design design that is the existence of the treatment group and control group. To obtain optimal development, the treatment group was given treatments 5 times while the control group did not get treatment. To obtain the appropriate data, the researchers collected data from the observation, documentation, and instruments of the creative development of children. The subjects were 2 classes of A1 as a treatment group with 10 children consisting of 4 males and 6 females, and A2 group as a control group with 8 children consisting of 4 males and 4 females. The results of this study at the pre-test stage that is for the group A1 57.37% and group A2 54.37%. In the post-test stage, after the treatment group received treatment, the result of the A1 group was 74.25% and the A2 group 56.40%. The final result of the comparison of pre-test and post-test that is treatment group (A1) has increased 16,88% while the control group (A2) only 2.03%. Through the utilization of educational game tool that is the image media in children's learning activities, teachers are able to increase the creativity of children aged 4-5 years. So that the utilization of educational media game tools will affect the creativity of children aged 4-5 years in children age national country city Mataram West Nusa Tenggara.DOI: http://doi.org/10.31098/ijeiece.v1i2.15